2019
DOI: 10.20944/preprints201912.0386.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosome Release of Drugs: Coupling with Epithelial-Mesenchymal Transition

Abstract: Extracellular vesicles (EVs), such as exosomes or oncosomes are released with molecules unfavorable for survival from cells. In addition, accumulating evidence has shown that tumor cells often eject anti-cancer drugs such as chemotherapeutics and targeted drugs within EVs, a novel mechanism of drug resistance. The EV-releasing, drug resistance phenotype is often coupled with cellular dedifferentiation and transformation, cells undergoing epithelial-mesenchymal transition (EMT) and taking on a cancer stem cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 90 publications
(119 reference statements)
1
0
0
Order By: Relevance
“…CDC37 could positively regulate EMT and exosome release through permitting the function of these protein kinases. Consistently, recent studies have shown that EMT in cancer cells was often coupled with exosome release and drug resistance [20,93,94].…”
Section: Discussionsupporting
confidence: 58%
“…CDC37 could positively regulate EMT and exosome release through permitting the function of these protein kinases. Consistently, recent studies have shown that EMT in cancer cells was often coupled with exosome release and drug resistance [20,93,94].…”
Section: Discussionsupporting
confidence: 58%